2021
DOI: 10.1016/j.jds.2020.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Platelet rich fibrin as a gingival tissue regeneration enhancer

Abstract: Tissue regenerative procedures aim to enhance regeneration of altered tissue. Extensive research has been carried out in this area and all proposed procedures present limitations. In this context the area of platelet-rich fibrin (PRF) research has gained tremendous awareness in the latest years. PRF is a low-cost regenerative modality that facilitates soft tissue regeneration derived from 100% autologous sources. It forms a fibrin mesh that liberates growth factors in a slow and prolonged manner and also conta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…Sharma et al (50) recorded that PRF is significantly better in promoting soft tissue healing and hastens bone formation in extraction socket. Similarly, Petrescu BN (51) proved the efficacy of PRF as a wound healing accelerator of gingival tissue. In comparison to gelatin sponge, results showed high statistical significant difference (p=.001).…”
Section: Discussionmentioning
confidence: 94%
“…Sharma et al (50) recorded that PRF is significantly better in promoting soft tissue healing and hastens bone formation in extraction socket. Similarly, Petrescu BN (51) proved the efficacy of PRF as a wound healing accelerator of gingival tissue. In comparison to gelatin sponge, results showed high statistical significant difference (p=.001).…”
Section: Discussionmentioning
confidence: 94%
“…Publications over the last few years concerning platelet-rich fibrin include practically all the fields of dentistry. It has been used for treating the perforation of the bottom of the pulp cavity in combination with MTA, multiple gingival recessions, or periodontal diseases [22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have reported other biological properties of L-PRF, such as enhancing wound healing, diminishing post-operative pain and minimizing the risk of infection ( Bi et al., 2020 ; Petrescu et al., 2021 ). Furthermore, recent research in this also reported an antimicrobial effect of L-PRF against key periodontal pathogens ( Castro et al., 2019b ).…”
Section: Introductionmentioning
confidence: 99%